To the question of the effect of isotretinoin on the neuropsychic state of patients with acne - Alexey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Patients with acne often develop neuropsychiatric disorders of varying severity, correlating, as a rule, with the severity of dermatosis. Isotretinoin is the most commonly used drug for the treatment of moderate acne. Due to the fact that in a number of studies isotretinoin was considered as a trigger for the development of various neuropsychiatric disorders, numerous studies were conducted to prove this possibility or to refute it. An analysis of the literature showed that, according to the vast majority of studies, isotretinoin does not lead to neuropsychiatric disorders. However, given the opposite opinion of some authors, it is advisable to actively identify, including in the anamnesis, any psycho-emotional disorders, and monitor them during therapy. In these cases, it is indicated to start treatment with small doses (recommendations have not been developed).